Parental Knowledge and Attitudes About Universal Lipid Screening Among Children Aged 9 to 11 Years. (May 2020) - Kern, Leah; Eichberger, Lisa; Wang, Helen; Lin, Tuo; Rhee, Kyung E.
Nationally recommended universal lipid screening (ULS) in children aged 9 to 11 years is low. Little is known about parents' understanding of screening. We conducted a survey exploring parental knowledge and attitudes regarding ULS. Of 91 parent respondents, 81.3% were female, 69.2% were non-Hispanic white, 90.1% had a college/graduate degree, and 63.7% had a family history of abnormal cholesterol. Overall, 45.5% agreed that ULS should be done for all children, 30.8% disagreed, and 23.1% were unsure. Parents' support for ULS was significantly associated with their attitudes toward screening rather than their knowledge about cholesterol, family history of cardiovascular disease or abnormal cholesterol, age, race/ethnicity, or gender. Parents were less likely to agree that ULS should be done if they thought that cholesterol screening should be done based on a child's health or family history rather than for all children ( P < .001), or if they thought that cholesterol screening was unnecessary ( P < .001).